2015
DOI: 10.1128/aem.00509-15
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Reduction of Norovirus and Male-Specific Coliphage Concentrations in Wastewater Treatment Plants

Abstract: Model results indicated that the mean WWTP influent concentration of NoV GII (3.9 log 10 gc/liter; 95% credible interval [CI], 3.5, 4.3 log 10 gc/liter) is larger than the value for NoV GI (1.5 log 10 gc/liter; 95% CI, 0.4, 2.4 log 10 gc/liter), with large variations occurring from one WWTP to another. For WWTPs with mechanical systems and chlorine disinfection, mean log 10 reductions were ؊2.4 log 10 gc/liter (95% CI, ؊3.9, ؊1.1 log 10 gc/liter) for NoV GI, ؊2.7 log 10 gc/liter (95% CI, ؊3.6, ؊1.9 log 10 gc/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 56 publications
4
70
0
1
Order By: Relevance
“…The concentration of NoV GII in the influent was higher than that of GI, which is in accordance with previous reports and epidemiological trends in the United States and globally (3,8,(35)(36)(37)(38). Epidemiological data in the United States and worldwide have shown that NoV outbreaks peak in the colder winter months, with 55% of the cases in the United States occurring in December to February (35,39), and is in agreement with our observation of high NoV GII densities (5.6 log 10 GC/100 ml) in the influent in November to March and with previous reports (3, 37, 40, 41).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The concentration of NoV GII in the influent was higher than that of GI, which is in accordance with previous reports and epidemiological trends in the United States and globally (3,8,(35)(36)(37)(38). Epidemiological data in the United States and worldwide have shown that NoV outbreaks peak in the colder winter months, with 55% of the cases in the United States occurring in December to February (35,39), and is in agreement with our observation of high NoV GII densities (5.6 log 10 GC/100 ml) in the influent in November to March and with previous reports (3, 37, 40, 41).…”
Section: Discussionsupporting
confidence: 81%
“…These findings indicate that virus removal was impacted negatively by the initial viral loads and positively by the environmental temperature. Virus removal fluctuated over time and was in accordance with previous studies (6,36,37,49). Compared with NoV GII strains, the GI strains seemed to be approximately 4.8 times more resistant to the two-stage wastewater treatment.…”
Section: Figsupporting
confidence: 72%
See 2 more Smart Citations
“…; Pouillot et al . ). This is because they have several characteristics in common with enteric viruses.…”
Section: Introductionmentioning
confidence: 97%